Relationship between Metallic Implants and Cancer: A Case-Control Study in a Canine Population - Li, X. Q.; Horn, D. L.; Black, J.; Stevenson, Sharon (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
To assess the possible role of metallic implants in the development of local, systemic and remote site cancer, a case-controlled study was conducted in a canine population. The cases consisted of 222 dogs with tumours of any kind, preceded by a fracture and fixation between January 1979 and December 1990. The controls consisted of 1635 dogs who had fracture and fixation for fracture without a later development of tumour during the same time period, randomly selected from the same database. Age was found to be a strong positive predictor for the development of tumours. A significant protective effect on tumours other than bone and soft tissue tumour development was seen associated with internal fixation (P <0.05). There was not a significant increase of risk associated with metal materials for the development of bone and soft tissue tumours. Further study is needed to address the local effect of metallic implants on the development of bone and soft tissue tumours.A case-control study was conducted to assess the relationship of metallic implants and the development of cancer in a canine population. No significant positive association was found between metal materials and the development of bone and soft tissue tumours.
Keywords: Fracture; metallic implants; cancer; case-control study; local and systemic effects